Diseño y construcción de un prototipo de antebrazo robótico mediante un control de programación - Guillén Figueroa, Inrving Javier (2017)
Science has technological advances that are surprising because through these solutions are given to countless problems: doctors, scientists, technicians, among others. Replacement of limbs, both in humans and animals, has been a reality for many years. In the early 1960s, biotechnology and robotics allowed the creation of the first robotic hand demonstrating a great contribution to humanity. From that moment until the present moment there has been an accelerated development in the biomechanics, getting to have people who live with this type of prosthesis and have a normal life. The project focuses on the design, construction and control of a robotic forearm by programming Arduino UNO boards, achieving the operation of electronic components such as flexural sensors, NRF24L01 wireless connection modules and servomotors. This project for teaching purposes will allow teaching in the Faculty of Mechanical Engineering of the State Technical University of Quevedo, and generate a close link between theory and practice in teaching robotics, according to the technological development that occurs worldwide, because it is an innovate pedagogical tool. In the design of the pieces, the software SOLIDWORKS 2017is used and the printing of these is executed, for the construction with 3D software WOX SINDOH that allow validating 3D models in STL format. The ABS polymer is the raw material to capture the idea. Finally, in the forearm is developed programming in the software allowing to obtain the appropriate technical movements wireless.